Cnesterodon holopteros (Cyprinodontiformes: Poeciliidae: Poeciliinae), a new species from the Republic of Uruguay - Lucinda, Paulo H.f.; Litz, Thomas; Recuero, Roberto (Zootaxa, 2006)
Cnesterodon holopteros new species is described from the río Uruguai drainage. The new species is distinguished from its congeners by: (1) a series of small dark brown dots along predorsal portion of first, second or third lateral scale row, associated with vertical bars along body sides; (2) eight or nine (rarely seven) dark brown vertical bars (from one to three scales in depth) along lateral surface of body in females, which may extend nearly down to belly (i.e., at level of ventral profile); (3) bony style at male gonopodium tip long and gently arched, narrowing towards tip to form a distal filament and bearing a V-shaped membrane restricted to its proximal third; (4) four branchiostegal rays in females; and (5) unbranched pelvic-fin rays.